PENINGKATAN MINAT BELAJAR DAN PEMAHAMAN MAHASISWA MELALUI PENERAPAN PROBLEM-BASED LEARNING - Ali Muhson (Jurnal Kependidikan, 2009)
This study was aimed at finding out the effects of problem-based learning (PBL) method to increase the students learning interests and achievement in advanced statistics. The study was conducted by classroom action research in two cycles. Data were analyzed using descriptive statistics. Findings showed that the implementation of the PBL method was able to increase the students learning interests both inside and outside the class. By way of case analysis tasks, students showed great participation in the teaching learning process. The PBL method also increased the students achievement. The students showed great understanding of the concepts and application of advanced statistics